Radiation-induced vascular malformations in the brain, mimicking tumor in MRI-based treatment response assessment maps (TRAMs). (February 2019) - Guez, David; Last, David; Daniels, Dianne; Sharabi, Shirley; Nass, Dvora; Nissim, Ouzi; Spiegelmann, Roberto; Tzarfaty, Galia; Hoffmann, Chen; Talianski, Alisa; Shoshan, Yigal; Fellig, Yakov; et al.
Highlights: Of 310 brain tumors patients recruited, histology of 99 lesions was available. Of those, 5 were histologically confirmed as radiation-induced malformations. TRAMs cannot differentiate active tumor from vascular malformation.